(untitled) (El-Wahat Journal for Research and Studies, 2026)
This study develops a socio-technical framework for digital transformation in media organizations, integrating theoretical insights with empirical barrier research. Drawing upon socio-technical systems design thinking, the framework addresses technological affordances, organizational structures, and social dynamics influencing transformation outcomes. Seven critical barrier dimensions are identified: missing skills, technical constraints, organizational misalignment, cultural resistance, structural mismatch, regulatory restrictions, and market limitations. The framework emphasizes joint optimization of technical and social systems, moving beyond technology-centric solutions. Findings demonstrate that successful digital transformation requires simultaneous consideration of human factors, technological infrastructure, and institutional change processes rather than isolated implementations, providing strategic guidance for media organizations navigating digital disruption.